2022
DOI: 10.1210/clinem/dgac303
|View full text |Cite
|
Sign up to set email alerts
|

Isocaloric-restricted Mediterranean Diet and Chinese Diets High or Low in Plants in Adults With Prediabetes

Abstract: Context Calorie restriction plus dietary advice is suggested as a preventive strategy for individuals with obesity and prediabetes, however, optimal diet is still debatable. We aimed to compare the effects of Mediterranean diet (MD) and Chinese diets high or low in plants on body weight and glucose homeostasis among high risk Chinese. Subjects and Methods In this parallel-arm randomized controlled trial, 253 Chinese adults ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In our study, the wb-TRS could well predict dynamic changes in glucose metabolism in response to 6 months of 25% calorie restriction dietary intervention in overweight/obese subjects [23]. In our trial (DPMH), a 25% calorie restriction produced an appreciable weight reduction and improved glucose homeostasis [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the wb-TRS could well predict dynamic changes in glucose metabolism in response to 6 months of 25% calorie restriction dietary intervention in overweight/obese subjects [23]. In our trial (DPMH), a 25% calorie restriction produced an appreciable weight reduction and improved glucose homeostasis [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the wb-TRS could well predict dynamic changes in glucose metabolism in response to 6 months of 25% calorie restriction dietary intervention in overweight/obese subjects [23]. In our trial (DPMH), a 25% calorie restriction produced an appreciable weight reduction and improved glucose homeostasis [23]. Calorie restriction improves cardiometabolic risk including atherogenic dyslipidemia (elevated triglycerides and fasting glucose, reduced HDL-C, diabetes, hypertension, and large waist circumference) [30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, PD spatially clustered in areas where the traditional Jiangnan diet is located; however, PD was different from the higher intake of wheat and processed meat [ 11 , 38 , 62 ]. We speculated that PD might represent a North–South fusion diet since people in developed areas, such as the Yangtze River Delta region and urban areas, might integrate diverse dietetic cultures, which in turn enriched local diets [ 10 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…215 Studies have demonstrated that the benefits of the traditional Jiangnan diet for reducing weight, BP, and blood glucose levels are comparable to those of the Mediterranean diet and that the benefits for preventing hypoglycemia and maintaining nocturnal glucose homeostasis are superior to those of the Mediterranean diet. 216 Other studies have demonstrated that the Jiangnan diet is also effective in reducing loss of muscle mass, preventing sarcopenia, and promoting healthy aging compared with other Chinese diets that allow the consumption of red meat and beans. 217 The traditional Japanese diet, "washoku," consists of one bowl of rice, one bowl of soup, and one main and two side dishes.…”
Section: Traditional Asian Dietsmentioning
confidence: 99%